3D‐Zipped Interface: In Situ Covalent‐Locking for High Performance of Anion Exchange Membrane Fuel Cells. Issue 22 (11th October 2021) - Liang, Xian; Ge, Xiaolin; He, Yubin; Xu, Mai; Shehzad, Muhammad A.; Sheng, Fangmeng; Bance‐Soualhi, Rachida; Zhang, Jianjun; Yu, Weisheng; Ge, Zijuan; Wei, Chengpeng; Song, Wanjie; et al.
Abstract: Polymer electrolyte membrane fuel cells can generate high power using a potentially green fuel (H2 ) and zero emissions of greenhouse gas (CO2 ). However, significant mass transport resistances in the interface region of the membrane electrode assemblies (MEAs), between the membrane and the catalyst layers remains a barrier to achieving MEAs with high power densities and long‐term stabilities. Here, a 3D‐interfacial zipping concept is presented to overcome this challenge. Vinylbenzyl‐terminated bi‐cationic quaternary‐ammonium‐based polyelectrolyte is employed as both the anionomer in the anion‐exchange membrane (AEM) and catalyst layers. A quaternary‐ammonium‐containing covalently locked interface is formed by thermally induced inter‐crosslinking of the terminal vinyl groups. Ex situ evaluation of interfacial bonding strength and in situ durability tests demonstrate that this 3D‐zipped interface strategy prevents interfacial delamination without any sacrifice of fuel cell performance. A H2 /O2 AEMFC test demonstration shows promisingly high power densities (1.5 W cm −2 at 70 °C with 100% RH and 0.2 MPa backpressure gas feeds), which can retain performances for at least 120 h at a usefully high current density of 0.6 A cm −2 . Abstract : A 3D‐interfacial zipping design is reported to in situ fabricate interfacial covalently locked membrane electrode assembly by thermally induced inter‐crosslinking of the terminal vinyl groups of the ionomer in the catalyst layers and the anion‐exchange membrane. Ex situ evaluation of interfacial bonding strength and in situ durability tests demonstrate that the 3D‐zipped interface strategy prevents interfacial delamination without any sacrifice of fuel cell performance.